Penerapan Bantuan Hukum bagi Masyarakat Marginal - Safawi, Imam; Prasetyo, Adrial Adam (Universitas Islam Negeri Alauddin Makassar, 2024)
Legal aid is the constitutional right of every citizen to guarantee protection and equality before the law, as a means of recognizing human rights (HAM). Obtaining legal assistance for everyone is a manifestation of access to justice as an implementation of guaranteed legal protection and guarantee of equality before the law. This is in accordance with the objectives of the legal aid concept which is linked to the ideals of a prosperous country. Legal aid is also an important instrument in the Criminal Justice System because it is part of protecting human rights for every individual, including the right to legal aid. For underprivileged people, the government has provided free or free legal assistance. However, many marginalized communities do not know this so they feel they are not being helped by the government. This study is based on normative legal research, namely research carried out by reviewing and analyzing legal materials and legal issues related to the problem under study. Legal research is carried out to solve problems that arise, while the results to be achieved are in the form of a description of what should be done to answer these problems. This article explains further about what legal aid is, how to apply for legal aid, and who can get free or free legal aid.